Determinants of African farmers’ strategies for adapting to climate change: multinomial choice analysis - Hassan, Rashid M.; Nhemachena, Charles (African Journal of Agricultural and Resource Economics, 2008)
This study analyzed determinants of farm-level climate adaptation measures in Africa using a multinomial choice model fitted to data from a cross-sectional survey of over 8000 farms from 11 African countries. The results indicate that specialized crop cultivation (mono-cropping) is the agricultural practice most vulnerable to climate change in Africa. Warming, especially in summer, poses the highest risk. It encourages irrigation, multiple cropping and integration of livestock. Increased precipitation reduces the probability of irrigation and will benefit most African farms, especially in drier areas. Better access to markets, extension and credit services, technology and farm assets (labor, land and capital) are critical for helping African farmers adapt to climate change. Government policies and investment strategies must support education, markets, credit and information about adaptation to climate change, including technological and institutional methods, particularly for poor farmers in the dry areas of Africa.
Keywords: openalex:import

Determinants of African farmers’ strategies for adapting to climate change: multinomial choice analysis - Hassan, Rashid M.; Nhemachena, Charles (African Journal of Agricultural and Resource Economics, 2008)
This study analyzed determinants of farm-level climate adaptation measures in Africa using a multinomial choice model fitted to data from a cross-sectional survey of over 8000 farms from 11 African countries. The results indicate that specialized crop cultivation (mono-cropping) is the agricultural practice most vulnerable to climate change in Africa. Warming, especially in summer, poses the highest risk. It encourages irrigation, multiple cropping and integration of livestock. Increased precipitation reduces the probability of irrigation and will benefit most African farms, especially in drier areas. Better access to markets, extension and credit services, technology and farm assets (labor, land and capital) are critical for helping African farmers adapt to climate change. Government policies and investment strategies must support education, markets, credit and information about adaptation to climate change, including technological and institutional methods, particularly for poor farmers in the dry areas of Africa.
Keywords: openalex:import

Determinants of African farmers’ strategies for adapting to climate change: multinomial choice analysis - Hassan, Rashid M.; Nhemachena, Charles (African Journal of Agricultural and Resource Economics, 2008)
This study analyzed determinants of farm-level climate adaptation measures in Africa using a multinomial choice model fitted to data from a cross-sectional survey of over 8000 farms from 11 African countries. The results indicate that specialized crop cultivation (mono-cropping) is the agricultural practice most vulnerable to climate change in Africa. Warming, especially in summer, poses the highest risk. It encourages irrigation, multiple cropping and integration of livestock. Increased precipitation reduces the probability of irrigation and will benefit most African farms, especially in drier areas. Better access to markets, extension and credit services, technology and farm assets (labor, land and capital) are critical for helping African farmers adapt to climate change. Government policies and investment strategies must support education, markets, credit and information about adaptation to climate change, including technological and institutional methods, particularly for poor farmers in the dry areas of Africa.
Keywords: openalex:import

Determinants of African farmers’ strategies for adapting to climate change: multinomial choice analysis - Hassan, Rashid M.; Nhemachena, Charles (African Journal of Agricultural and Resource Economics, 2008)
This study analyzed determinants of farm-level climate adaptation measures in Africa using a multinomial choice model fitted to data from a cross-sectional survey of over 8000 farms from 11 African countries. The results indicate that specialized crop cultivation (mono-cropping) is the agricultural practice most vulnerable to climate change in Africa. Warming, especially in summer, poses the highest risk. It encourages irrigation, multiple cropping and integration of livestock. Increased precipitation reduces the probability of irrigation and will benefit most African farms, especially in drier areas. Better access to markets, extension and credit services, technology and farm assets (labor, land and capital) are critical for helping African farmers adapt to climate change. Government policies and investment strategies must support education, markets, credit and information about adaptation to climate change, including technological and institutional methods, particularly for poor farmers in the dry areas of Africa.
Keywords: openalex:import

Determinants of African farmers’ strategies for adapting to climate change: multinomial choice analysis - Hassan, Rashid M.; Nhemachena, Charles (African Journal of Agricultural and Resource Economics, 2008)
This study analyzed determinants of farm-level climate adaptation measures in Africa using a multinomial choice model fitted to data from a cross-sectional survey of over 8000 farms from 11 African countries. The results indicate that specialized crop cultivation (mono-cropping) is the agricultural practice most vulnerable to climate change in Africa. Warming, especially in summer, poses the highest risk. It encourages irrigation, multiple cropping and integration of livestock. Increased precipitation reduces the probability of irrigation and will benefit most African farms, especially in drier areas. Better access to markets, extension and credit services, technology and farm assets (labor, land and capital) are critical for helping African farmers adapt to climate change. Government policies and investment strategies must support education, markets, credit and information about adaptation to climate change, including technological and institutional methods, particularly for poor farmers in the dry areas of Africa.
Keywords: openalex:import; openalex:yes

Determinants of African farmers’ strategies for adapting to climate change: multinomial choice analysis - Hassan, Rashid M.; Nhemachena, Charles (African Journal of Agricultural and Resource Economics, 2008)
This study analyzed determinants of farm-level climate adaptation measures in Africa using a multinomial choice model fitted to data from a cross-sectional survey of over 8000 farms from 11 African countries. The results indicate that specialized crop cultivation (mono-cropping) is the agricultural practice most vulnerable to climate change in Africa. Warming, especially in summer, poses the highest risk. It encourages irrigation, multiple cropping and integration of livestock. Increased precipitation reduces the probability of irrigation and will benefit most African farms, especially in drier areas. Better access to markets, extension and credit services, technology and farm assets (labor, land and capital) are critical for helping African farmers adapt to climate change. Government policies and investment strategies must support education, markets, credit and information about adaptation to climate change, including technological and institutional methods, particularly for poor farmers in the dry areas of Africa.
Keywords: openalex:import

How can African agriculture adapt to climate change: Micro-level analysis of farmers’ adaptation to climate change in Southern Africa: - Nhemachena, Charles; Hassan, Rashid M. (Research briefs, 2008)
Agricultural production remains the main source of livelihood for rural communities in Sub-Saharan Africa, providing employment to more than 60 percent of the population and contributing about 30 percent of gross domestic product. With likely long-term changes in rainfall patterns and shifting temperature zones, climate change is expected to significantly affect agricultural production, which could be detrimental to the region’s food security and economic growth. An assessment of the factors influencing farm-level adaptation can facilitate the formation of policies and investment strategies that help moderate potential adverse consequences of long-term climate change. Because smallholder farmers tend to have a low capacity to adapt to changes in climatic conditions, policies that help these farmers adapt to global warming and associated climatic extremes are particularly important.This brief is based on a study that assesses smallholder farmers’ adaptation to climate change in southern Africa. The study identifies farmers’ perceptions of climate change and the determinants of farm-level adaptation strategies, and recommends policies that could help stabilize national and regional food production given the anticipated adverse effects of climate change.
Keywords: openalex:import

Measuring Ethiopian farmers’ vulnerability to climate change across regional states - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study analyzes the vulnerability of Ethiopian farmers to climate change based on the integrated vulnerability assessment approach using vulnerability indicators. The vulnerability indicators consist of the different socioeconomic and biophysical attributes of Ethiopia's seven agriculture-based regional states. The different socioeconomic and biophysical indicators of each region collected have been classified into three classes, based on the Intergovernmental Panel on Climate Change's (IPCC 2001) definition of vulnerability, which consists of adaptive capacity, sensitivity, and exposure. The results indicate that the relatively least-developed, semiarid, and arid regions—namely, Afar and Somali—are highly vulnerable to climate The Oromia region—a wide region characterized both by areas of good agricultural production in the highlands and midlands and by recurrent droughts, especially in the lowlands—is also vulnerable. The Tigray region, which is characterized by recurrent drought, is also vulnerable to the negative impacts of climate change in comparison with the other regions. Thus, investing in the development of the relatively underdeveloped regions of Somali and Afar, irrigation for regions with high potential, early warning systems to help farmers better cope in times of drought, and production of drought-tolerant varieties of crops and species of livestock can all reduce the vulnerability of Ethiopian farmers to climate change. from authors' abstract
Keywords: openalex:import

How can African agriculture adapt to climate change: Climate variability and maize yield in South Africa: - Akpalu, Wisdom; Hassan, Rashid M.; Ringler, Claudia (Research briefs, 2008)
Maize is the primary food staple in southern Africa, and 50 percent of the total maize output in the area is produced in South Africa, where maize constitutes approximately 70 percent of grain production and covers 60 percent of the country's cropping area. Climate change could have a significant impact on South African maize production. The scientific community has established that the temperature in South Africa increased significantly between 1960 and 2003 (by 0.13 degrees Celsius), and further temperature increases and changes in the quantity and pattern of rainfall are expected despite any attempts by the international community to reduce greenhouse gas emissions. Although the maize plant is quite hardy and adaptable to harsh conditions, warmer temperatures and lower levels of precipitation could have detrimental effects on yields, thereby increasing food insecurity in the region. This brief is based on a paper that uses household survey data to explore the direct impact of climate variability, measured by changes in temperature and precipitation, on maize yields in the Limpopo Basin of South Africa.
Keywords: openalex:import

How can African agriculture adapt to climate change: Measuring Ethiopian farmers’ vulnerability to climate change across regional states [in Amharic]: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (Research briefs, 2008)
agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country’s economy. It constitutes more than half the nation’s gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia’s dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change. from text
Keywords: openalex:import

Measuring Ethiopian farmers' vulnerability to climate change across regional states [in Amharic]: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country's economy. It constitutes more than half the nation's gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia's dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change. from text
Keywords: openalex:import

Measuring Ethiopian farmers' vulnerability to climate change across regional states [in Amharic]: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia (Research briefs, 2008)
agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country's economy. It constitutes more than half the nation's gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia's dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change. from text
Keywords: openalex:import

Climate Change and Agriculture in Africa: Impact Assessment and Adaptation Strategies - Dinar, Ariel; Hassan, Rashid M.; Mendelsohn, Robert; Benhin, James (2008)
Foreword * Introduction and Rationale * Study Objectives, Structure, Methodology, Organization and Countries Agroclimatic Conditions * Methods and Models Developed and Used in the Study * Results of the Country Analyses * Results of the Regional Analyses * Summary, Conclusions and Policy Implications * Index
Keywords: openalex:import

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
Keywords: openalex:import

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
Keywords: openalex:import

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
Keywords: openalex:import

Analyzing the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Alemu, Tekie; Yesuf, Mahmud; Ringler, Claudia (RePEc: Research Papers in Economics, 2008)
This study identifies the major methods used by farmers to adapt to climate change in the Nile Basin of Ethiopia, the factors that affect their choice of method, and the barriers to adaptation. The methods identified include use of different crop varieties, tree planting, soil conservation, early and late planting, and irrigation. Results from the discrete choice model employed indicate that the level of education, gender, age, and wealth of the head of household; access to extension and credit; information on climate, social capital, agroecological settings, and temperature all influence farmers' choices. The main barriers include lack of information on adaptation methods and financial constraints. Moreover, the analysis reveals that age of the household head, wealth, information on climate change, social capital, and agroecological settings have significant effects on farmers' perceptions of climate change. from authors' abstract
Keywords: openalex:import

How can African agriculture adapt to climate change: Analysis of the determinants of farmers' choice of adaptation methods and perceptions of climate change in the Nile Basin of Ethiopia: - Deressa, Temesgen; Hassan, Rashid M.; Ringler, Claudia; Alemu, Tekie; Yesuf, Mahmud (Research briefs, 2008)
Ethiopia's agricultural sector, which is dominated by smallscale, mixed-crop, and livestock farming, is the mainstay of the country's economy. It constitutes more than half of the country's gross domestic product, generates more than 85 percent of foreign exchange earnings, and employs about 80 percent of the population. Unfortunately, Ethiopia's dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. Thus, a deeper understanding of the complex interdependence between changing climatic conditions and Ethiopia's agricultural sector- together with adaptation options-is crucial. Additional information about farmers' awareness of climate change and current adaptation approaches would assist policymakers in their efforts to decrease the country's vulnerability to the adverse impacts of climate change. This brief is based on a study that endeavors to guide policymakers on ways to promote greater adaptation by identifying the household characteristics that increase farmers' awareness of climate change and influence farmers' decision to adapt.
Keywords: openalex:import

A Ricardian Analysis Of The Distribution Of Climate Change Impacts On Agriculture Across Agro-Ecological Zones In Africa - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Hassan, Rashid M.; Kurukulasuriya, Pradeep (2008)
This paper examines the distribution of climate change impacts across the six- teen Agro-Ecological Zones (AEZs) of Africa. We combine net revenue from livestock and
Keywords: openalex:import

Differential Adaptation Strategies To Climate Change In African Cropland By Agro-Ecological Zones - Seo, S. Niggol; Mendelsohn, Robert; Kurukulasuriya, Pradeep; Dinar, Ariel; Hassan, Rashid M. (2008)
This paper quantifies how African farmers have adapted their crop and irrigation decisions to their farm's current agro-ecological zone. The results indicate that farmers carefully consider the climate and other conditions of their farm when making these choices. These results are then used to forecast how farmers might change their irrigation and crop choice decisions if climate changes. The model predicts African farmers would adopt irrigation more often under a very hot and dry climate scenario but less often with a mild and wet scenario. However, farms in the deserts, lowland humid forest, or mid elevation humid forest would reduce irrigation even in the very hot and dry climate scenario. Area under fruits and vegetables would increase Africa-wide with the very hot and dry climate scenario, except in the lowland semi-arid agro-ecological zone. Millet would increase overall under the mild and wet scenario, but decline substantially in the lowland dry savannah and lowland semi-arid agro-ecological zones. Maize would be chosen less often across all the agro-ecological zones under both climate scenarios. Wheat would decrease across Africa. The authors recommend that care must be taken to match adaptations to local conditions because the optimal adaptation would depend on the agro-ecological zone and the climate scenario.
Keywords: openalex:import

A Ricardian Analysis of the Distribution of Climate Change Impacts on Agriculture Across Agro-Ecological Zones in Africa - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Hassan, Rashid M.; Kurukulasuriya, Pradeep (Social Science Research Network, 2008)
This paper examines the distribution of climate change impacts across the 16 agro-ecological zones in Africa using data from the Food and Agriculture Organization combined economic survey data from a Global Environment Facility/World Bank project. Net revenue per hectare of cropland is regressed on a set of climate, soil, and socio-economic variables using different econometric specifications with and without country fixed effects. Country fixed effects slightly reduce predicted future climate related damage to agriculture. With a mild climate scenario, African farmers gain income from climate change; a more severe scenario, they lose income. Some locations are more affected than others. The analysis of agro-ecological zones implies that the effects of climate change will vary across Africa. For example, currently productive areas such as dry/moist savannah are more vulnerable to climate change while currently less productive agricultural zones such as humid forest or sub-humid zones become more productive in the future. The agro-ecological zone classification can help explain the variation of impacts across the landscape.
Keywords: openalex:import

Differential adaptation strategies to climate change in African cropland by agro-ecological zones - Seo, S. Niggol; Mendelsohn, Robert; Kurukulasuriya, Pradeep; Dinar, Ariel; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2008)
This paper quantifies how African farmers have adapted their crop and irrigation decisions to their farm's current agro-ecological zone. The results indicate that farmers carefully consider the climate and other conditions of their farm when making these choices. These results are then used to forecast how farmers might change their irrigation and crop choice decisions if climate changes. The model predicts African farmers would adopt irrigation more often under a very hot and dry climate scenario but less often with a mild and wet scenario. However, farms in the deserts, lowland humid forest, or mid elevation humid forest would reduce irrigation even in the very hot and dry climate scenario. Area under fruits and vegetables would increase Africa-wide with the very hot and dry climate scenario, except in the lowland semi-arid agro-ecological zone. Millet would increase overall under the mild and wet scenario, but decline substantially in the lowland dry savannah and lowland semi-arid agro-ecological zones. Maize would be chosen less often across all the agro-ecological zones under both climate scenarios. Wheat would decrease across Africa. The authors recommend that care must be taken to match adaptations to local conditions because the optimal adaptation would depend on the agro-ecological zone and the climate scenario.
Keywords: openalex:import